Screening of deep eutectic solvents (DESs) as green CO2 sorbents: from solubility to viscosity. (8th December 2016) - Sarmad, Shokat; Xie, Yujiao; Mikkola, Jyri-Pekka; Ji, Xiaoyan
Abstract : 35 novel DESs are synthesized and screened in terms of their CO2 solubility and viscosity. Abstract : Deep eutectic solvents (DESs) as ionic liquid (IL) analogues show great potential for CO2 capture. They exhibit favorable solvent properties and are considered to be economical alternatives to conventional ILs. In this study, we prepare 35 DESs and screen them in terms of their CO2 solubility and viscosity, both crucial factors to be considered when designing efficient CO2 sorbents. The influence of salt and HBD type and structure, as well their molar ratio on the CO2 solubility and viscosity of the DESs is investigated. The viscosity and CO2 solubility of the DESs are compared with those of other DESs and conventional ILs. 15 DESs, which exhibit comparable CO2 absorption capacity to choline chloride–urea DESs, glycerol DESs and fluorinated ILs, are chosen as the promising ones. The viscosities of the selected DESs are below 200 mPa s and are lower than those of choline chloride-based DESs. Since the viscosity of the DESs is relatively high, on a par with those of conventional ILs, the effect of water as a co-solvent is investigated in order to decrease the viscosity. The addition of water to the glycerol-based DESs improves the kinetics of absorption by decreasing the viscosity, thus increasing the CO2 absorption capacity. Dry or aqueous DESs that demonstrate a high sorption capacity and low viscosity are chosen for additional analysis and characterization, and further functionalization will be carried out in the future to improve their sorption capacity.